Non-Peripheral Octa-Zinc(II) Phthalocyanine: Synthesis and investigation of Photosensitizer Potential - Kulu, Irem (Gazi Univ, 2022)
New compounds 3,6-bis(2-azidoethoxy)phthalonitrile and 1,4,8,11,15,18,22,25-octakis-(2-azidoethoxy) phthalocyaninato zinc(II) were synthesized and characterized by general spectroscopic methods such as UV-Vis, FT-IR, H-1 NMR and mass spectrometry. Moreover, photosensitizer ability for photodynamic therapy applications; singlet oxygen photosensitizer, photodegradation and fluorescence abilities of 14,8,11,15,18,22,25-octakis-(2-azidoethoxy) phthalocyaninato zinc(II) molecule were investigated and reported.
Non-Peripheral Octa- Zinc(II) Phthalocyanine: Synthesis and investigation of Photosensitizer Potential
Keywords: Azido phthalocyanine; Fluorescence; Singlet oxygen; Photophysical; Photochemical